Identity: its integral study - Meza Ingar, Carmen (2020)
The identity is a right exercised before the entire human race and, despite this important fact, in the field of social organization, social classes have been widely studied from a Western viewpoint and according to income per capita, in other words, establishing socioeconomic characteristics and ignoring the valuation of the cultural elements of the primitive groups and indigenous peoples. As a result, we presently refer to groups excluded from exercising their rights and to the existence of second-class citizens